The complete Martial Arts Student - Sprague Martina (Untied States : Equilibrium Books, 2007)
Examines the learning process and gives the martial arts student hundreds of examples and solutions to problems he or she will encounter during training. More importantly, the aim of the book is to start the student on the road to becoming a critical thinker, a person who can use the highest stage of learning correlation to accelerate his or her education in the martial arts.
Keywords: Martial Arts